The Development of Office Inventory System by Using Office Registration Material Program for office of the Science and Technology, Nakhon Pathom Rajabhat University - Thapthim, Sukanya (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aims to 1. Study the process of developing system for disbursement office supplies by using Office Registration Material Program for office supplies. 2. Comparing satisfaction evaluation form before and after using Office Registration Material Program for office supplies. The researcher collected data from faculty, staff and students of the Faculty of Science and Technology. Nakhon Pathom Rajabhat University, 400 people with convenient selection methods The research results find that 1 Study on the process of the develop the system for disbursement office supplies by using Office Registration Material Program for office of the Science and Technology, Nakhon Pathom Rajabhat University that in keeping control with Faculty of Science and Technology. 2) The results of the satisfaction evaluation form of the customer before using Office Registration Material Program for office supplies, Service procedure is moderate, mean = 2.77. Accuracy is moderate with a mean = 2.63 and resources at the lowest value, with a mean = 2.45. And after assessment of satisfaction evaluation form, service procedure at the highest level, mean = 4.76. Accuracy, mean = 4.80, and resources, mean = 4.23 Article history : Received 8 May 2018 Revised 7 September 2018 Accepted 10 September 2018 SIMILARITY INDEX = 0.00